Breaching the Alps: the Roman Idea of the ‘Wall of Italy’ from the Republic to the Augustan Era - Lampinen Antti (Juraj Dobrila University of Pula, 2022)
The Roman preoccupation with the Alps as the tutamen of Italy owed its epistemic immediacy to a much more recent event—the Cimbric Wars (113-101 BCE). This traumatic episode had reawakened imagery of the northern enemies penetrating the “Wall of Italy,” which in some cases went all the way back to the Mid-Republican narrative traditions of the Gallic Invasions and the much more frequently debated shock of Hannibal’s invasion. The significance of this imagery continued even beyond the Augustan era, so that remnants of the same Roman insecurity about the “Wall of Italy” being breached, especially by northerners, are preserved in narratives about later Julio-Claudians such as Caligula and Nero. This article first looks at the likely origins of the idea of the Alps as the “Wall of Italy” in Middle-Republican perceptions, projected back onto the past and presenting Rome as predestined to dominate Italy and the Gauls in particular as external intruders in the peninsula. Next, the Late Republican and Augustan stages of the motif is reviewed, and the impact of the Cimbric Wars on this imagery is debated. Finally, there will be brief discussion of anecdotes found in Tacitus and Suetonius about later Julio-Claudian episodes in which the fear of a northern invasion breaching the Alps seem to have gripped the Romans.